2015
DOI: 10.1177/1049732315593549
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Adherence

Abstract: Dominant health care professional discourses on cancer take for granted high levels of individual responsibility in cancer prevention, especially in expectations about preventive screening. At the same time, adhering to screening guidelines can be difficult for lower-income and under-insured individuals. Colorectal cancer (CRC) is a prime example. Since the advent of CRC screening, disparities in CRC mortality have widened along lines of income, insurance, and race in the United States. We used a community-eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…This result was not anticipated, but it is consistent with public health research demonstrating that structural barriers, such as lack of employer-paid leave in the U.S., can thwart patients’ desire and intentions to obtain needed healthcare [33]. Further research needs to identify the interpersonal, institutional, and policy conditions under which medications that have physically challenging side effects are most likely to be perceived as most aversive.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This result was not anticipated, but it is consistent with public health research demonstrating that structural barriers, such as lack of employer-paid leave in the U.S., can thwart patients’ desire and intentions to obtain needed healthcare [33]. Further research needs to identify the interpersonal, institutional, and policy conditions under which medications that have physically challenging side effects are most likely to be perceived as most aversive.…”
Section: Discussionsupporting
confidence: 63%
“…Although the resulting component structure was very similar to the one obtained with unstandardized ratings (see Supplemental Material), the Components 3 and 4 were considerably less interpretable. In addition the regression results accounted for less variance and were less consistent with public health research regarding the role of structural barriers in health decisions [33]. Therefore, we base our main conclusions on the analyses with the nonstandardized responses.…”
mentioning
confidence: 75%
“…These factors are described in the published literature and were discussed extensively by stakeholders and audience members at both conference sessions. Specifically, patients who do not have access to reliable transportation, sufficient healthcare coverage, paid leave from work, and alternative childcare or eldercare services may not be able to choose a desired option because doing so is either logistically infeasible or has such severe negative consequences for other aspects of their lives that the choice is practically infeasible (Hunleth et al, 2016; Lara et al, 2001). One stakeholder reported that rural patients facing a diagnosis of ductal carcinoma in situ of the breast may choose mastectomy over lumpectomy plus radiation in part because it was not possible to make multiple trips to the treatment center located three hours away: “If three quarters of your patients do not have paid time off, then the choices they are making are not your clinical outcome choices.…”
Section: Research Recommendationsmentioning
confidence: 99%
“…Some decision aids and patient education materials have been criticized for emphasizing individual decision making and responsibility while also overlooking structural factors that can constrain patients’ decisions (Hunleth et al, 2016). Providing information without considering structural constraints can cause emotional distress, as recounted by one stakeholder: “a patient who…[became aware] of treatment options that were not actually viable, practical options for her [due to structural constraints] explicitly said, ‘I wish you had not told me this.…”
Section: Research Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation